Теплопередавальні характеристики двофазних мініатюрних термосифонів з нанорідинами - Kravets, Vladimir; Hurov, Dmytro (PE "Politekhperiodika", Book and Journal Publishers, 2020)
This paper presents and analyzes experimental data on the total thermal resistances of two-phase miniature thermosyphons with nanofluids; the geometric parameters of the thermosyphons for all experimental samples are identical: total length 700 mm, internal diameter 5 mm. The following nanofluids used as heat carriers are: aqueous nanofluid based on carbon nanotubes, aqueous nanofluid based on synthetic diamond, and aqueous nanofluid based on amorphous carbon. Much attention is also paid to the influence of the filling ratio on the heat transfer characteristics of the thermosyphons. The influence of filling ratio and types of nanofluid on the performance of miniature closed two-phase thermosyphons is demonstrated.